Robust methoxy-based covalent organic frameworks membranes enable efficient near-molecular-weight selectivity - Yanqing Xu; Jiaqi Xiong; Chenfei Lin; Yixiang Yu; Qite Qiu; Junbin Liao; Huimin Ruan; Arcadio Sotto; Jiangnan Shen (Advanced Membranes)
Uniform pore size is essential for molecular sieving in separation membranes. Traditional nanofiltration (NF) polymer membranes struggle with precise structure control due to random chain packing and rapid cross-linking, leading to varied pore sizes and poor molecular discrimination. Covalent organic frameworks (COFs) offer ordered porous structures for enhanced molecular selectivity. We synthesized composite COFs membranes with triphenylamine derivatives through interfacial polymerization, adjusting pore channel functional groups to achieve high water permeance and size-selective molecule retention. The TFB-OMe-TAPA COFs membrane demonstrated sharp rejection profiles, separating solutes of different molecular sizes. A three-stage cascade process was used to fractionate binary molecules with varying charges, achieving a separation factor of 26.7 for heterogeneous charge molecules. This work reveals the selectivity of COF membranes in near-molecular-weight systems, expanding their potential in molecular separations.